2012
DOI: 10.1152/ajpgi.00038.2012
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 signaling promotes both mucosal homeostatic and fibrotic responses during Salmonella-induced colitis

Abstract: GA, Vallance BA. MyD88 signaling promotes both mucosal homeostatic and fibrotic responses during Salmonella-induced colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…These observations suggest that RORα does not influence initial inflammatory responses, or the host's ability to clear the infection, but rather plays a specific role in generating a pro-fibrotic response in the gut during late stages of chronic Salmonella infection. The apparent disconnect between bacterial colonization the severity of fibrosis is consistent with previous reports which demonstrate that intestinal fibrosis does not require the presence of Salmonella as a persistent inflammatory stimulus (31,32). Instead, the pathology becomes self-propagating and is largely irrespective of interventions that attempt to reduce pathogen burdens or repress early inflammatory responses.…”
Section: Discussionsupporting
confidence: 89%
“…These observations suggest that RORα does not influence initial inflammatory responses, or the host's ability to clear the infection, but rather plays a specific role in generating a pro-fibrotic response in the gut during late stages of chronic Salmonella infection. The apparent disconnect between bacterial colonization the severity of fibrosis is consistent with previous reports which demonstrate that intestinal fibrosis does not require the presence of Salmonella as a persistent inflammatory stimulus (31,32). Instead, the pathology becomes self-propagating and is largely irrespective of interventions that attempt to reduce pathogen burdens or repress early inflammatory responses.…”
Section: Discussionsupporting
confidence: 89%
“…also described a colonic gene profile associated with both inflammation and fibrosis. COX-2 is a marker which for decades has clearly been associated with acute inflammation [25], [26], [27], [28] but which also increases significantly with time in fibrosis models, pulmonary fibrosis [29] and colonic fibrosis included [30]. In our observation a similar relationship between COX-2 and MR parameters linked both fibrosis and inflammation.…”
Section: Discussionsupporting
confidence: 73%
“…The two most commonly used mouse strains are C57/BL6 and BALB/c, but since these strains suffer from a loss-of-function mutation in their nramp1 genes, they are extremely susceptible to Salmonella infec- tion (6). Recently we have shown the applicability of the attenuated ⌬aroA strain of S. Typhimurium for studying colitis in these mouse strains (7). Our present studies found that Muc2 plays a critical role in host defense against S. Typhimurium.…”
Section: Discussionmentioning
confidence: 48%
“…It was surprising that Muc2 Ϫ/Ϫ mice succumbed to ⌬aroA S. Typhimurium, considering that infection by this pathogen is not normally lethal, even to severely immunodeficient mice (7,33). Considering that their symptoms (hunched appearance, piloerection, and reduced activity) observed during Salmonella infection are typically signs of a systemic disease (34), we decided to compare inflammatory responses within the livers of WT and Muc2 Ϫ/Ϫ mice.…”
Section: Muc2mentioning
confidence: 99%
See 1 more Smart Citation